A novel CRYGC E128* mutation underlying an autosomal dominant nuclear cataract in a south Indian kindred. (1st November 2020) - Kandaswamy, Dinesh Kumar; Vasantha, K.; Graw, Jochen; Santhiya, Sathiyaveedu Thyagarajan
ABSTRACT: Purpose: To identify the mutation causing an autosomal dominant congenital nuclear cataract in a south Indian family by whole exome sequencing and to characterize further phenotypically the same in a zebra fish model. Methods: A six-generation family (DKEC1) with several affected members registered at the Regional Institute of Ophthalmology (RIO), Chennai was documented to have congenital nuclear cataract. Detailed clinical history and blood samples were collected from all available family members. Genomic DNA of the proband was subjected to whole exome sequencing. Sequence variations suggestive of putative mutations were further confirmed by bidirectional sequencing and restriction site analysis. Functional analysis of the mutant CRYGC E128* in zebrafish embryos was done to dissect out the pathogenicity. Results: A unique variation viz., c.382 G > T in the coding region of the CRYGC gene, resulting in a premature stop codon at position 128 (E128*) was documented in the affected family members. The same was absent in unaffected family members and in 120 unrelated population controls checked. Bioinformatic tools predicted that the mutation might cause a deleterious effect on protein structure and function. Molecular function analysis of this novel mutation (p. E128*, CRYGC ) in the zebrafish indicated this mutation to impair lens transparency. Conclusion: This study identified a novel CRYGC mutation, E128* to cause autosomal dominant congenital nuclear cataract in a large south Indian family. Our study provides a new insight onto how the mutation might affect the γC-crystallin structure and function besides emphasizing the need for genetic diagnosis toward vision restoration.